Adaptasi Dewi Nyx Pada Tata Rias Wajah Fantasi Untuk Pesta Halloween - Haniifah, Yaasmiin Nuur (Jurnal Tata Rias, 2022)
Adaptation is the practice of turning an object into a work like making an object of the goddess Nyx as a fantasy make-up. Fantasy makeup is a make-up art that aims to shape the impression of a model's face into a imagined fantasy form, but is immediately recognized by the beholder. Fantasy makeup on the goddess Nyx was taken to display the image of the goddess Nyx, such as her symbol, aura, and emblem. This research has the aim of creating a new makeup look for the occasion of a Halloween night party and creating fantasy makeup with the source of the idea of ​​​​the adaptation of the goddess Nyx. In the end, this makeup is equipped with clothing and accessories that support it so that it becomes a unified whole to be worn at a Halloween night party. Halloween night party is all saints' night party which is currently used as a Cosplay party. The type of research used is research and development with the ADDIE model. The result of the research that has been done is that the adaptation of the goddess Nyx in fantasy makeup produces new makeup looks for the occasion of the Halloween night party.